2022
DOI: 10.1089/whr.2021.0124
|View full text |Cite
|
Sign up to set email alerts
|

The CANOVA Study Real-World Evidence of Biologic Treatments in Moderate-Severe Psoriasis in Italy: A Gender Perspective

Abstract: Background: In psoriasis, several studies have indicated sex differences in clinical characteristics, type of treatment, and outcomes. A higher impact of psoriasis on quality of life (QoL) and a lower treatment satisfaction have been reported in women by different authors. Objectives: This article reports the results of a post hoc gender analysis of CANOVA study, aimed at assessing 16/24/52-week effectiveness of biologics in patients with mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Our results reveal that these biologics were effective within these real-life settings, similar to previous reports. [26][27] In our study, the 3 biologics demonstrated comparable efficacy profiles in terms of the EMM DLQI reduction and PCS improvement.…”
Section: Discussionmentioning
confidence: 50%
“…Our results reveal that these biologics were effective within these real-life settings, similar to previous reports. [26][27] In our study, the 3 biologics demonstrated comparable efficacy profiles in terms of the EMM DLQI reduction and PCS improvement.…”
Section: Discussionmentioning
confidence: 50%